Impact of COVID-19 on household food insecurity and interlinkages with child feeding practices and coping strategies in Uttar Pradesh, India: a longitudinal community-based study. Issue 4 (21st April 2021) - Nguyen, Phuong Hong; Kachwaha, Shivani; Pant, Anjali; Tran, Lan M; Ghosh, Sebanti; Sharma, Praveen Kumar; Shastri, Vishal Dev; Escobar-Alegria, Jessica; Avula, Rasmi; Menon, Purnima
Abstract : Objectives: The COVID-19 pandemic has profound negative impacts on people's lives, but little is known on its effect on household food insecurity (HFI) in poor setting resources. This study assessed changes in HFI during the pandemic and examined the interlinkages between HFI with child feeding practices and coping strategies. Design: A longitudinal survey in December 2019 (in-person) and August 2020 (by phone). Setting: Community-based individuals from 26 blocks in 2 districts in Uttar Pradesh, India. Participants: Mothers with children <2 years (n=569). Main outcomes and analyses: We measured HFI by using the HFI Access Scale and examined the changes in HFI during the pandemic using the Wilcoxon matched-pairs signed-rank tests. We then assessed child feeding practices and coping strategies by HFI status using multivariable regression models. Results: HFI increased sharply from 21% in December 2019 to 80% in August 2020, with 62% households changing the status from food secure to insecure over this period. Children in newly or consistently food-insecure households were less likely to consume a diverse diet (adjusted OR, AOR 0.57, 95% CI 0.34 to 0.95 and AOR 0.51, 95% CI 0.23 to 1.12, respectively) compared with those in food-secure households. Households with consistent food insecurity were more likely to engage in coping strategies such as reducing other essential non-food expenditures (AOR 2.2, 95% CI 1.09 to 4.24), borrowing money to buy food (AOR 4.3, 95% CI 2.31 to 7.95) or selling jewellery (AOR 5.0, 95% CI 1.74 to 14.27) to obtain foods. Similar findings were observed for newly food-insecure households. Conclusions: The COVID-19 pandemic and its lockdown measures posed a significant risk to HFI which in turn had implications for child feeding practices and coping strategies. Our findings highlight the need for further investment in targeted social protection strategies and safety nets as part of multisectoral solutions to improve HFI during and after COVID-19.